Evaluación de extractos botánicos mediante técnica de hoja simple para control de sigatoka negra (mycosphaerella fijiensis morelet) en banano - Sánchez Valdivieso, Marcos Alcides (My University, 2022)
"Banana (Musa x paradisiaca) is a tropical fruit with high worldwide consumption for its quality, nutritional benefits and shelf life. Its leaves are affected by Black Sigatoka (BS, Mycosphaerella fijiensis Morelet), decreasing photosynthesis and yield. The application of organic fungicides was evaluated on the severity of Black Sigatoka in the banana crop in the rainy and dry season. The trial was carried out in Fumipalma, S.A., Guayas province, Ecuador. Plants of cv. Williams, sown at 3m x 2.5m (1,333 plants·ha-1). The applications began in plants with 12-14 leaves, in leaves 1 (L1) and 2 (L2), in the right part of the midrib (single leaf test methodology; SLT). A randomized complete block design of experiments with six treatments and four replications was used. The evolution of the disease (%, Fumipalma S.A.) and area under the disease progress curve (AUDPC) in L1 and L2 were evaluated. up to 35 and 56 days after application in the rainy and dry season, respectively. The evolution of the disease in L1 in SLT was between 16.60-50.00% and 4.30-77.80 (rain-drought). The area under the severity curve (AUDPC) presented statistical differences with values between 217.4-556.1 and 40.43-671.56 in L1 (rain and drought). The affected area was between 27.50-56.25% and 13.05 and 96.26 in L2 (rain and drought). The AUDPC presented significant statistical differences, the control was more affected. The application of organic fungicides generates control over BS, the percentage of affected area and the severity index of the disease in the control was higher. In L2 the severity of the disease was greater than in L1. The fungicides Progranic Cinnacar, Progranic Mega and Jaque Mate alone or combined with Volley showed the highest control of BS, both in the rainy and dry season."
El banano (Musa x paradisiaca) es un fruto tropical con alto consumo mundial por su calidad, beneficios nutricionales y vida en anaquel. Sus hojas son afectadas por Sigatoka negra (SN, Mycosphaerella fijiensis Morelet), disminuyendo fotosíntesis y rendimiento. Se evaluó la aplicación de fungicidas orgánicos sobre la severidad de Sigatoka negra en el cultivo de banano en época lluviosa y seca. El ensayo se realizó en Fumipalma, S.A., provincia de Guayas, Ecuador. Se utilizaron plantas del cv. Williams, sembradas a 3m x 2,5m (1333 plantas·ha-1). Las aplicaciones se iniciaron en plantas con 12-14 hojas, en las hojas 1 (H1) y 2 (H2), en la parte derecha de la nervadura central (metodología single leaf test; SLT). Se utilizó un diseño de experimentos en bloques completos al azar con seis tratamientos y cuatro repeticiones. Se evaluó la evolución de la enfermedad (%, Fumipalma S.A.) y área bajo la curva del progreso de la enfermedad (AUDPC) en H1 y H2. hasta 35 y 56 días después de la aplicación en época lluviosa y seca, respectivamente. La evolución de la enfermedad en H1 en SLT, estuvo entre 16,60-50,00% y 4,30-77,80 (lluvia-sequía). El área bajo la curva de severidad (AUDPC) presentó diferencias estadísticas con valores entre 217,4-556,1 y 40,43-671,56 en H1 (lluvia y sequía). El área afectada estuvo entre 27,50-56,25% y 13,05 y 96,26 en H2 (lluvia y sequía). El AUDPC presentó diferencias estadísticas significativas, el testigo fue más afectado. La aplicación de fungicidas orgánicos genera control sobre SN, el porcentaje de área afectada y elíndice de severidad de la enfermedad en el testigo fue mayor. En H2 la severidad de la enfermedad fue mayor que en H1. Los fungicidas Progranic Cinnacar, Progranic Mega y Jaque Mate solos o combinados con Volley presentaron el mayor control de SN, tanto en época lluviosa como seca.
Keywords: Fungicidas orgánicos; Sigatoka negra; Manejo; Época lluviosa y seca